Abstract 200: ICA Lesion Etiology does not affect the Outcomes after Endovascular Treatment of Acute Tandem LVO - Milagros R. Galecio Castillo; Mudassir Farooqui; Ameer Hassan; Mouhammad Jumaa; Afshin Divani; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo Guerrero; Amer Malik; James Siegler; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Tandem lesions (TLs) are present in up to 15% of patients with stroke due to acute large vessel occlusions.(1) Nevertheless, published research on endovascular treatment outcomes in this population is scarce. Although TLs are most commonly of atherosclerotic etiology, some patients present with dissection of the ICA.(2, 3) In this study, we compared the clinical outcomes of TL patients with the two etiologies. Methods A retrospective analysis was performed on a multicenter cohort of patients with TLs who underwent endovascular treatment. The patients were categorized into two groups according to the etiology of the ICA lesion: atherosclerosis and dissection. Patients were matched by baseline characteristics. Clinical outcomes, including recanalization success, functional independence and hemorrhagic events were assessed with multivariable analyses. Results Of 691 patients from the database, 526 met the inclusion criteria of this study. 467 (88.8%) patients presented with atherosclerosis of the ICA, and 59 (11.2%) patients presented dissection. Univariable differences were found in median age (69 y. [IQR 61 ‐ 76] vs. 52 y. [IQR 44 ‐ 63], p<.001), rates of hypertension (74.5% vs. 52.5%, p<0.001), hyperlipidemia (49.2% vs. 27.1%, p=.001), diabetes (29.8% vs. 15.3%, p=.019), and prior antiplatelets use (36.8% vs. 22.8%, p=.037). After matching and adjusting for confounders, we did not find differences between both groups for the main outcomes: Successful reperfusion (89.1% vs. 79.7%, aOR 0.46, 95% CI 0.20 – 1.08, p=.074), mRS 0‐2 at 90 days (47.5% vs. 47.4%, aOR 0.80, 95% CI 0.44 – 1.48, p=.381), and sICH (4.3% vs. 6.8%, aOR 0.96, 95% CI 0.17 – 5.58, p=0.965). Similarly, no differences were found for the secondary outcomes: Excellent recanalization (51.1% vs. 40.7%, aOR 0.86, 95% CI 0.46 – 1.60, p=.632), early neurological improvement (41% vs. 36.2%, aOR 0.76, 95% CI 0.40 – 1.43, p=.392), parenchymal hematoma type 2 (7.8% vs. 8.5%, aOR 0.59, 95% CI 0.17 – 2.03, p=.400), mortality at 90 days (17.4% vs. 14%, aOR 1.17, 95% CI 0.49 – 2.81, p=.726), and intrahospital mortality (9.6% vs. 8.6%, aOR 0.91, 95% CI 0.31 – 2.62, p=.859). Conclusion In our cohort, patients with lesions of atherosclerotic etiology achieved higher rates of successful and excellent recanalization, but the effect disappeared when matching the groups and adjusting for confounders. The results of this study show that the etiology of the ICA lesion does not affect the clinical outcomes of endovascular treatment in tandem lesions.